Acting Agentically at Work: Developing a Short Measure of Professional Agency - Vähäsantanen, Katja; Räikkönen, Eija; Paloniemi, Susanna; Hökkä, Päivi (Nordic Journal of Working Life Studies, 2022)
Although professional agency has become an increasingly crucial issue in work organizations, investigators lack a brief instrument to measure it. This paper introduces a short measure to explore professional agency at work. Our aim was to shorten the original 17-item Professional Agency Measure, while also exploring its usability for cross-validating questionnaire datasets, and investigating the relationship between professional agency and work engagement. Three dimensions of professional agency emerged, with three items per dimension, across the domains of healthcare, real estate services, and information technology (all within Finland). All the dimensions (Influencing at work, Participation at work, and Negotiating professional identity) showed good reliability. The results further revealed that these dimensions of agency are distinct from, but closely and positively linked to work engagement. In particular, our research offers a reliable, short measure of professional agency that is relevant across professional domains in the Nordic context.